LEXICAL AND CONTEXTUAL MEANINGS CONTAINED IN RELIGIOUS SONG LYRICS AT QUIVER CENTER ACADEMY (QCA) - Fitriani Ponno; Sari Rejeki; Maulana Taufik (Universitas Pakuan, 2019)
ABSTRACTThe purpose of this research is to study the theme, lexical and contextual meaning in the lyrics of the songs frequently sung in Quiver Center Academy (QCA) school, located in Gading Serpong, Tangerang city. This research uses descriptive analysis method. The analysis result in the conclusion that noun is the most category word that has lexical and contextual meaning in the songs. The main reason why these words have lexical and contextual meaning is to know the meaning of the song in a deeper way. Moreover, they also support the understanding of the theme in QCAs are divinity, destiny, integrity, victory, struggle, and dedication.Keyword: theme, lexical meaning, and contextual meaning.